2020
DOI: 10.1016/j.omtn.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

miR-548e Sponged by ZFAS1 Regulates Metastasis and Cisplatin Resistance of OC by Targeting CXCR4 and let-7a/BCL-XL/S Signaling Axis

Abstract: Ovarian cancer (OC) is a severe malignancy featuring a poor prognosis due to rapid metastasis and chemotherapy resistance. In this study, we extensively investigated the upstream and downstream mechanisms of miR-548e in regulating OC progression and cisplatin resistance. Our results indicated that ZFAS1 was highly expressed and promoted OC cell proliferation, migration, invasion, and cisplatin resistance by directly suppressing miR-548e expression. ZFAS1 co-localized with miR-548e in the cytosols of OC cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…19 Additionally, ZFAS1 is highly expressed and promotes ovarian cancer cell proliferation, migration, invasion, and cisplatin resistance by sponging miR-548e and elevating CXCR4 expression. 8 Here, we also identified miR-647 as a target of ZFAS1. ZFAS1 suppressed miR-647 expression and negatively correlated with miR-647 expression in CC tissues.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…19 Additionally, ZFAS1 is highly expressed and promotes ovarian cancer cell proliferation, migration, invasion, and cisplatin resistance by sponging miR-548e and elevating CXCR4 expression. 8 Here, we also identified miR-647 as a target of ZFAS1. ZFAS1 suppressed miR-647 expression and negatively correlated with miR-647 expression in CC tissues.…”
mentioning
confidence: 64%
“…7 In ovarian cancer, ZFAS1 is highly expressed and accelerate cell proliferation, migration, invasion, and induces cisplatin resistance by directly suppressing miR-548e expression. 8 ZFAS1 was found to be downregulated in breast tumors compared to normal tissue. 9 However, the expression pattern, clinical significance and molecular mechanism of ZFAS1 has not been thoroughly studied in CC.…”
Section: Introductionmentioning
confidence: 94%
“…Tolerability generated during chemotherapy such as apoptosis escape and Epithelial mesenchymal transformation (EMT), results in poor prognosis and is currently impeding the success of targeted therapies in cancer treatment [ 121 , 122 ]. Plenty of evidence suggested that Bcl-xL-dependent apoptotic inhibition was the main reason that promoted chemotherapy resistance in tumours in vitro and vivo (Table 2 ) [ 123 , 124 ]. A study on breast cancer showed that cells passed through EMT obtained therapeutic resistance by upregulating Bcl-xL transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting Bcl-xL expression in breast cancer cells enhanced the cytotoxicity and apoptosis induced by T-DM1 [ 126 ]. Additionally, increased CXCR4 expression in ovarian cancer induced cisplatin resistance through promoting Bcl-xL/S [ 123 ]. Upregulated Bcl-xL expression was also found to be involved in resistance to therapy targeting Bcl-2 in mantle-cell lymphoma and Acute Myelocytic Leukemia [ 57 , 127 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZFAS1 serves a role in atherosclerosis (15) and a variety of cancer types (16)(17)(18)(19), such as ovarian cancer, breast cancer, prostate cancer and hepatocellular carcinoma. ZFAS1 is a candidate biomarker predictive of the prognosis of thyroid carcinoma (20).…”
Section: Introductionmentioning
confidence: 99%